Odpowiedzi

Najlepsza Odpowiedź!
2010-03-10T00:22:14+01:00
4x - x(x-2) + 1/2(x²+3) = 2(x+3) - x(x-4)
4x - x² + 2x + ½x² + 1,5 = 2x + 6 - x² + 4x
6x - ½x² + 1,5 = 6x + 6 - x²
½x² - 4,5 = 0

Δ=-4*½*(-4,5) = 9

x₁=-3/1 = -3
x₂= 3/1 = 3
2010-03-10T00:26:03+01:00
4x-x(x-2)+1/2(x²+3)=2(x+3)-x(x-4)
4x-x²+2x+½x²+1 ½= 2x + 6 - x² + 4x
6x-½x²+½=6x+6-x²
½x²-4½ = 0

Δ=b²-4ac
Δ=-4 ½ (-4½) = 9

x₁=-3/1=-3
x₂= 3/1=3
2010-03-10T00:57:28+01:00
4x-x(x-2)+1/2(x²+3)=2(x+3)-x(x-4) /*2
8x-2x(x-2)+(x²+3)=4(x+3)-2x(x-4)
8x-2x²+4x+x²+3=4x+12-2x²+8x
-x²+12x+3=-2x²+12x+12
-x²+2x²+3-12=0
x²-9=0
(x-3)(x+3)=0
x-3=0
x=3

lub
x+3=0
x=-3